Some Properties of Fuzzy Quasimetric Spaces - Abdul Mohamad (International Journal of Mathematics and Mathematical Sciences)
Some properties of fuzzy quasimetric spaces are studied. We prove that the topology induced by any 0𝑥0005𝑒𝑀-complete fuzzy-quasi-space is a 0𝑥0005𝑒𝑑-complete quasimetric space. We also prove Baire's theorem, uniform limit theorem, and second countability result for fuzzy quasi-metric spaces.